A SPL Infrastructure for Supporting Scientific Experiments in Petroleum Reservoir Research Field - Foschiani, Fernanda Yara dos Santos; Tizzei, Leonardo Pondian; Rubira, Cecília Mary Fischer (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2013)
Computational resources are commonly used in the research field, in order to facilitate data and services sharing. The frequent study of new research methodologies, the softwarediversity, simulators and data involved in experiments, lead to the necessity of environments that provide facilities for technology use and matching. Aiming to support the software diversity, the proposed solution is a scientific workflow environment that allows the researchers to create their own personalized workflows, using components provided by the development team as well as developed by themselves, regardless of the language being used. The basis for this environment is a component based software product line. The proposed extractive method for the product line development is supported by a software reengineering framework and uses existing modeling techniques. One case study was performed to evaluate some aspects, including the components reuse enhancement and the workflow customization capability. This study case had a positive result, showing that the proposedsolution allows the researchers to customize their workflows.